Bambu Sebagai Material Fleksibel - I Putu Yoga Ananta Nugraha; I Putu Candra Suta Adnyana; I Wayan Rendy Saputra; Made Anggita Wahyudi Linggasani; Made Mas Surya Wiguna (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2021)
In the world of architecture, the use of materials is one of the things that must be considered in designing buildings. In the field of tectonics, the choice of material as a structure is important. Materials that we often see such as wood, concrete, iron and others are the preparation of the basic elements of the building structure. But today there is another material that will be a substitute for the material mentioned above, namely bamboo. Bamboo itself is often encountered, it indicates that bamboo is a material that is easy to find and has its own characteristics. Many people know that bamboo is a flexible, unique and universal material as a building material. In addition, there are other reasons why bamboo can be chosen because it is a renewable material and pollutes the environment less than today's modern materials. With this research, it is hoped that it can build an alibi for people who consider bamboo as a low-class material and incompetent compared to similar materials. This study will explain how bamboo can be compared with similar materials and also the advantages if bamboo is used as a building material or structure.